(untitled) (CIPEEX, 2025)
Sedentarism is characterized by a lifestyle with low physical fitness adherence, according to the World Health Organization (WHO); nearly one-third of the global population over 15 years old engages in insufficient physical activity for their needs, with approximately 800,000 deaths related to physical inactivity. Awareness of the sedentary lifestyle and its consequences remains high despite widespread information dissemination. Low engagement in active living is influenced by environmental factors and general habits, such as excessive use of technology. The pursuit of health and well-being has led to lifestyle changes, creating trends like "summer projects" that propagate misinformation from unqualified influencers, leading to abrupt changes and harmful guidance (Ministry of Health, 2022). The present study aims to identify musculoskeletal causes and impacts on the body of a sedentary person. The methodology involves an integrative literature review of articles published from January 2020 to May 2024, encompassing publications highlighting the harms of sedentary behavior and consequences of inadequate physical activity. Findings indicated that incorrect exercise or exceeding one’s current physical capacity can cause cardiovascular stress, joint, and muscle injuries. To prevent such risks, it is recommended to initiate physical activities gradually and under professional guidance. Physiotherapy plays a crucial role in injury prevention, treatment, promoting flexibility, coordination, and autonomy. In conclusion, exercise should be personalized to ensure safety and effectiveness, preventing injuries and promoting well-being. Awareness of the risks of physical inactivity and the importance of a gradual transition to active living are essential to reduce sedentary rates and improve public health.